2013
DOI: 10.1121/1.4789936
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of individual tigers (Panthera tigris) from long distance roars

Abstract: This paper investigates the extent of tiger (Panthera tigris) vocal individuality through both qualitative and quantitative approaches using long distance roars from six individual tigers at Omaha's Henry Doorly Zoo in Omaha, NE. The framework for comparison across individuals includes statistical and discriminant function analysis across whole vocalization measures and statistical pattern classification using a hidden Markov model (HMM) with frame-based spectral features comprised of Greenwood frequency cepst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Spectrograms (consisting of discrete Fourier transforms of short, frequently overlapped, segments of the signal) are ubiquitous and characterise well those acoustic features related to spectral profile and frequency modulation, many of which are relevant in animal acoustic communication. Examples of such features include minimum and maximum fundamental frequency, slope of the fundamental frequency, number of inflection points, and the presence of harmonics (Oswald et al ., ) that vary, for example, between individuals (Buck & Tyack, ; Blumstein & Munos, ; Koren & Geffen, ; Ji et al ., ; Kershenbaum, Sayigh & Janik, ; Root‐Gutteridge et al ., ), and in different environmental and behavioural contexts (Matthews et al ., ; Taylor, Reby & McComb, ; Henderson, Hildebrand & Smith, ).…”
Section: Acoustic Unitsmentioning
confidence: 99%
“…Spectrograms (consisting of discrete Fourier transforms of short, frequently overlapped, segments of the signal) are ubiquitous and characterise well those acoustic features related to spectral profile and frequency modulation, many of which are relevant in animal acoustic communication. Examples of such features include minimum and maximum fundamental frequency, slope of the fundamental frequency, number of inflection points, and the presence of harmonics (Oswald et al ., ) that vary, for example, between individuals (Buck & Tyack, ; Blumstein & Munos, ; Koren & Geffen, ; Ji et al ., ; Kershenbaum, Sayigh & Janik, ; Root‐Gutteridge et al ., ), and in different environmental and behavioural contexts (Matthews et al ., ; Taylor, Reby & McComb, ; Henderson, Hildebrand & Smith, ).…”
Section: Acoustic Unitsmentioning
confidence: 99%
“…Although this can be done automatically using state of the art deep learning techniques (Stowell et al 2018), acoustic features are often extracted manually, whereby simple summary variables (e.g. min, max and mean) associated with the fundamental frequency and the harmonics are calculated (Fan et al 2019;Ji et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition models are assessed based on their ability to classify the 'unseen' calls correctly. Several algorithms have been used for this purpose, including discriminant functions (Blumstein and Munos 2005;Fan et al 2019), artificial neural networks (Mielke and Zuberbühler 2013;Reby et al 1998), gaussian mixture models (Cheng et al 2010) and hidden Markov models (Clemins et al 2005;Ji et al 2013). One of the main issues affecting the classification performance of vocal recognition models is the presence of background noise.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the distinctive alarm calls of some species are acoustically unique to different types of danger171819. Other studies have exemplified the ability to distinguish between emitting individuals based on acoustic features of their vocalizations202122232425262728293031, while several studies, mainly in primates, revealed subtle context-dependent acoustic modifications of calls in everyday behaviors, such as food-related behaviors32, agonistic interactions33, and long-distance calls29.…”
mentioning
confidence: 99%